Determinants Of Village Midwife's Performance On The Quality Of Antenatal Care (ANC) Services In The Region West Pasaman District Year 2024 - Nurul Maulidia; Bambang Setiaji (Jurnal EduHealth, 2024)
This study aims to analyze the situation of the influence of knowledge, motivation and workload on the quality of antenatal care services in the West Pasaman Regency area in 2023 with a focus on efforts to improve maternal health, through ANC care. which is intended for pregnant women to care for and maintain the health of themselves and their babies periodically. According to the 2021 West Pasaman Regency Health Profile, there were 31 cases of maternal deaths in West Pasaman Regency, consisting of 14 cases of deaths of pregnant women, 10 cases of deaths of postpartum women and 7 cases of deaths of postpartum women. The number of maternal deaths in 2021 is higher than in 2020 with 18 cases of maternal death. The development of the maternal mortality rate per 100,000 live births in the last 10 years has generally increased. This research uses quantitative methods to explore the influence of knowledge, motivation and workload on the quality of antenatal care services, based on recent data showing low ANC achievements. In fact, according to data, the number of midwives available and spread throughout the sub-districts in West Pasaman Regency is quite a lot, namely 270 people. Therefore, it is necessary to follow up regarding the quality of midwife services in providing ANC to mothers during the pregnancy to birth process. The research results show that work motivation and workload influence the quality of antenatal care services in the West Pasaman Regency area in 2023. Meanwhile, knowledge has no influence on the quality of services. The conclusion of the study emphasizes the importance of additional knowledge regarding compliance with ANC service standards, which was initially only 7T, now increased to 10T. As well as additional knowledge regarding ANC examinations, which were initially only 4x during pregnancy, to 6x during pregnancy, as well as system improvements made by the health department. related to increasing work motivation. Such as increases in rank and salary, as well as the convenience of a service system that is increasingly systematic and uses technology.